An Enhanced Anonymity Control Scheme based on Quantum Cryptography in Cloud Environment - Reddy, V Sreenija; A, Revathi; kumar, Phani N (International Journal of Computer Sciences and Engineering, 2020)
Cryptography is widely used technique to provide security in large networks like cloud environments. Classical cryptography and quantum cryptography are two widely used techniques. Classical cryptography uses simple mathematical methods to provide security. So it is more vulnerable to several attacks such as eaves dropping, man-in-the-middle attack etc. But in classical cryptography digital signatures are used to provide best authentication. Quantum cryptography uses quantum mechanical properties to provide security. It uses photons and polarization but it requires more communication rounds. So by combing classical and quantum cryptography to show a new combination. Here we can use implicit user authentication, explicit mutual authentication and we can digital signatures to provide best authentication. The main objectives of this article are design and develop an enhanced anonymity control scheme based on quantum cryptographic techniques. EANCTRL- an enhanced anonymity control scheme based on Quantum key distribution is presented in this article.